UPDATE OF ANURANS SPECIES OF SÃO NICOLAU FARM, MATO GROSSO, BRAZIL - J. C. Noronha; M. M. Lima; C. L. Velasquez; E. J. Almeida; A. B. Barros; D. J. Rodrigues (Scientific Electronic Archives, 2015)
The Anurofauna at São Nicolau farm was sampled at 30 points by time constrained audio-visual search (TAVS) and pitfall traps with drift fence (PFDF). The farm presents a rich diversity of species of anurans (53), being the type locality of Amazophrynella vote, recently described, and the area of the first record in Brazil of Hyalinobatrachium cappellei. The number of species found in this study is similar to other Amazonian localities. Most species have basal reproductive mode, type 1, with eggs and aquatic larvae. This study represents an important contribution to the knowledge and conservation of frogs of South of Amazonia, because it is carried out in an area with few studies about on anurofauna and that shows the rapid transformation of habitats, due to the expansion of agricultural activities.